Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Let's analyze each equation to determine whether it is quadratic. Quadratic equations are in the form [tex]\( ax^2 + bx + c = 0 \)[/tex], where [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] are constants, and [tex]\( a \neq 0 \)[/tex].
1. Equation: [tex]\(5x^2 + 15x = 0\)[/tex]
This equation is already in the standard form [tex]\(5x^2 + 15x = 0\)[/tex], which matches the quadratic form [tex]\( ax^2 + bx + c = 0 \)[/tex] with [tex]\( a = 5 \)[/tex], [tex]\( b = 15 \)[/tex], and [tex]\( c = 0 \)[/tex].
Therefore, [tex]\(5x^2 + 15x = 0\)[/tex] is a quadratic equation.
2. Equation: [tex]\(6x - 1 = 4x + 7\)[/tex]
Simplifying this equation:
[tex]\[ 6x - 4x - 1 = 7 \implies 2x - 1 = 7 \implies 2x = 8 \implies x = 4 \][/tex]
This is a linear equation because it does not contain an [tex]\( x^2 \)[/tex] term.
Therefore, [tex]\(6x - 1 = 4x + 7\)[/tex] is not a quadratic equation.
3. Equation: [tex]\(x^2 - 4x = 4x + 7\)[/tex]
Simplifying this equation:
[tex]\[ x^2 - 4x - 4x = 7 \implies x^2 - 8x = 7 \implies x^2 - 8x - 7 = 0 \][/tex]
This is in the standard form of a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex] with [tex]\( a = 1 \)[/tex], [tex]\( b = -8 \)[/tex], and [tex]\( c = -7 \)[/tex].
Therefore, [tex]\(x^2 - 4x = 4x + 7\)[/tex] is a quadratic equation.
4. Equation: [tex]\(2x - 1 = 0\)[/tex]
This equation is in the form [tex]\(2x - 1 = 0\)[/tex], which is a linear equation with no [tex]\( x^2 \)[/tex] term.
Therefore, [tex]\(2x - 1 = 0\)[/tex] is not a quadratic equation.
5. Equation: [tex]\(3x^2 + 5x - 7 = 0\)[/tex]
This equation is already in the standard form [tex]\(3x^2 + 5x - 7 = 0\)[/tex], which matches the quadratic form [tex]\( ax^2 + bx + c = 0 \)[/tex] with [tex]\( a = 3 \)[/tex], [tex]\( b = 5 \)[/tex], and [tex]\( c = -7 \)[/tex].
Therefore, [tex]\(3x^2 + 5x - 7 = 0\)[/tex] is a quadratic equation.
6. Equation: [tex]\(x^3 - 2x^2 + 1 = 0\)[/tex]
This equation is in the form [tex]\(x^3 - 2x^2 + 1 = 0\)[/tex], which contains a cubic term [tex]\( x^3 \)[/tex]. Since it has a term with [tex]\( x \)[/tex] raised to the third power, it is not a quadratic equation.
Therefore, [tex]\(x^3 - 2x^2 + 1 = 0\)[/tex] is not a quadratic equation.
In summary, the following equations are quadratic:
- [tex]\(5x^2 + 15x = 0\)[/tex]
- [tex]\(x^2 - 4x = 4x + 7\)[/tex]
- [tex]\(3x^2 + 5x - 7 = 0\)[/tex]
So, the quadratic equations are:
1. [tex]\(5 x^2 + 15 x = 0\)[/tex]
2. [tex]\(x^2 - 4 x = 4 x + 7\)[/tex]
3. [tex]\(3 x^2 + 5 x - 7 = 0\)[/tex]
1. Equation: [tex]\(5x^2 + 15x = 0\)[/tex]
This equation is already in the standard form [tex]\(5x^2 + 15x = 0\)[/tex], which matches the quadratic form [tex]\( ax^2 + bx + c = 0 \)[/tex] with [tex]\( a = 5 \)[/tex], [tex]\( b = 15 \)[/tex], and [tex]\( c = 0 \)[/tex].
Therefore, [tex]\(5x^2 + 15x = 0\)[/tex] is a quadratic equation.
2. Equation: [tex]\(6x - 1 = 4x + 7\)[/tex]
Simplifying this equation:
[tex]\[ 6x - 4x - 1 = 7 \implies 2x - 1 = 7 \implies 2x = 8 \implies x = 4 \][/tex]
This is a linear equation because it does not contain an [tex]\( x^2 \)[/tex] term.
Therefore, [tex]\(6x - 1 = 4x + 7\)[/tex] is not a quadratic equation.
3. Equation: [tex]\(x^2 - 4x = 4x + 7\)[/tex]
Simplifying this equation:
[tex]\[ x^2 - 4x - 4x = 7 \implies x^2 - 8x = 7 \implies x^2 - 8x - 7 = 0 \][/tex]
This is in the standard form of a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex] with [tex]\( a = 1 \)[/tex], [tex]\( b = -8 \)[/tex], and [tex]\( c = -7 \)[/tex].
Therefore, [tex]\(x^2 - 4x = 4x + 7\)[/tex] is a quadratic equation.
4. Equation: [tex]\(2x - 1 = 0\)[/tex]
This equation is in the form [tex]\(2x - 1 = 0\)[/tex], which is a linear equation with no [tex]\( x^2 \)[/tex] term.
Therefore, [tex]\(2x - 1 = 0\)[/tex] is not a quadratic equation.
5. Equation: [tex]\(3x^2 + 5x - 7 = 0\)[/tex]
This equation is already in the standard form [tex]\(3x^2 + 5x - 7 = 0\)[/tex], which matches the quadratic form [tex]\( ax^2 + bx + c = 0 \)[/tex] with [tex]\( a = 3 \)[/tex], [tex]\( b = 5 \)[/tex], and [tex]\( c = -7 \)[/tex].
Therefore, [tex]\(3x^2 + 5x - 7 = 0\)[/tex] is a quadratic equation.
6. Equation: [tex]\(x^3 - 2x^2 + 1 = 0\)[/tex]
This equation is in the form [tex]\(x^3 - 2x^2 + 1 = 0\)[/tex], which contains a cubic term [tex]\( x^3 \)[/tex]. Since it has a term with [tex]\( x \)[/tex] raised to the third power, it is not a quadratic equation.
Therefore, [tex]\(x^3 - 2x^2 + 1 = 0\)[/tex] is not a quadratic equation.
In summary, the following equations are quadratic:
- [tex]\(5x^2 + 15x = 0\)[/tex]
- [tex]\(x^2 - 4x = 4x + 7\)[/tex]
- [tex]\(3x^2 + 5x - 7 = 0\)[/tex]
So, the quadratic equations are:
1. [tex]\(5 x^2 + 15 x = 0\)[/tex]
2. [tex]\(x^2 - 4 x = 4 x + 7\)[/tex]
3. [tex]\(3 x^2 + 5 x - 7 = 0\)[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.